The Ratio Of Exrended Spectrum Beta Lactamase Among Various Gram Negative Bacilli isolated from Urine Specimens - Tekerekoğlu, Mehmet S.; Taştekin, Neşe; Kuzucu, Çiğdem; Abut, Latife; Tevfik, Mehmet; Durmaz, Bengül; Özerol, İ. Halil (Fırat University, 2001)
The purpose of this study was to determine the ratio of ex'rended spectrum beta lactamase (ESBL) among Gram negative bacilli which were isolated from urine specimens. E.coli were found as the most common agents in inpatients and outpatients. In both patient groups, the high ESBL ratio was determined in Klebsiella spp.

İdrar numunelerinden izole edilen Gram negatif çomaklarda genişlemiş spektrumlu beta-laktamaz oranını saptamak amacıyla bu çalışma yapıldı. Poliklinik ve yatan hastalarda en sık etken E.coli olarak saptandı. Her iki hasta grubunda en yüksek GSBL oranı Klebsiella türlerinde saptanmıştır.
İDRAR NUMUNELERİNDEN İZOLE EDİLEN ÇEŞİTLİ GRAM NEGATİF ÇOMAKLARDA GENİŞLEMİŞ SPEKTRUMLU BETA- LAKTAMAZLARIN ORANI